Dental Laboratory Technology Education in China: Current Situation and Challenges. Issue 3 (1st March 2013) - Zheng, Liwei; Yue, Li; Zhou, Min; Yu, Haiyang
Abstract : Modern dentistry and dental education in China were first introduced from abroad by Dr. Lindsay in 1907. However, advancements in the field of dental laboratory technology did not occur to the same degree in specialties such as prosthodontics and orthodontics. Since the 1990s, orders from abroad demanding dental appliances surged as the image of China as the "world's factory" strengthened. The assembly line model, in which technicians work like simple procedure workers, was rapidly applied to denture production, while the traditional education system and apprenticeship systems demonstrated little progress in these years. The lack of advancement in dental laboratory technology education caused insufficient development in China's dental technology industry. In order to alter the situation, a four‐year dental laboratory technology undergraduate educational program was established in 2005 by West China School of Stomatology, Sichuan University (WCSS, SCU). This program was based on SCU's undergraduate education and WCSS's junior college education systems. The program introduced scientific methods in relevant subjects into laboratory technicians' training and made many improvements in the availability of trained faculty, textbooks, laboratory facilities, and curriculum.